2011
DOI: 10.5194/nhess-11-1669-2011
|View full text |Cite
|
Sign up to set email alerts
|

Comparing historical-hydrogeomorphological reconstitution and hydrological-hydraulic modelling in the estimation of flood-prone areas – a case study in Central Portugal

Abstract: Abstract. The Arunca River basin in Central Portugal has a historical record of hazardous events related to floods, causing widespread disturbance. This article describes the application of two approaches based on well-known methods for the estimation of flood-prone areas: (i) historicalhydrogeomorphological reconstitution, applied to the entire Arunca River basin, and (ii) hydrological-hydraulic modelling, applied to four sections selected from different (upper, middle and lower) sectors of the basin and incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…Floods account for about one third of all geophysical hazards globally and adversely affect more people than any other natural hazards (Adhikari et al, ; Smith & Ward, ). They are a major concern in many regions around the world (Santos, Tavares, & Andrade, ), particularly in Latin America (Alcantara‐Ayala, ; Filizola et al, ). In Chile, 71% of the floods that occurred between 1574 and 2012 were caused by extreme rainfall events (Rojas, Mardones, Arumí, & Aguayo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Floods account for about one third of all geophysical hazards globally and adversely affect more people than any other natural hazards (Adhikari et al, ; Smith & Ward, ). They are a major concern in many regions around the world (Santos, Tavares, & Andrade, ), particularly in Latin America (Alcantara‐Ayala, ; Filizola et al, ). In Chile, 71% of the floods that occurred between 1574 and 2012 were caused by extreme rainfall events (Rojas, Mardones, Arumí, & Aguayo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have combined methods, which can yield better results because the technique can compensate for the limitations of individual methods. Notable results have been achieved, for example, by combining historical and geomorphological methods (Luino et al, 2002b) or geomorphological and hydrological methods (Chen and Simons, 1986;Townsend and Walsh, 1998;Lastra et al, 2008;Lelièvre et al, 2008;Chouari, 2009;Ballard et al, 2011) or by an approach based on historical-hydrogeomorphological reconstitution and hydrological-hydraulic modelling (Santos et al, 2011).…”
mentioning
confidence: 99%
“…buildings, roads, walls and river network) were used. Santos et al (2011) reported that the 1-dimensional hydraulic modelling process using Hec-Ras (steady unidirectional flow) requires a detailed digital elevation model (DEM); Warner, Brunner, Wolfe, and Piper (2009) recommend using 1:10,000 scale data or contour lines of 5 m. An accurate DEM of 1 m pixel size was generated, which was used to produce the necessary geometric elements for the hydraulic modelling. For modelling the flood-prone areas, it was necessary to create the geometric data corresponding to: (i) the geometric centre of the channel, (ii) the river banks and water flow direction, delineated from the DEM; (iii) the cross-sections (260 with an average distance between them of 16 m), obstructions to flow such as walls, weirs and buildings, the location of the bridges and non-contributory areas; (iv) the land use map (COS2007) published by the Portuguese Geographic Institute (IGP, 2010) and the Manning n values corresponding to the type of land use (Brunner, 2008;van der Sande, de Jong, & de Roo, 2003).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The guide also provides methodologies to apply in the cartographic representation of flood hazard maps. In Portugal, studies about floods are particularly focused on the delineation of flood-prone areas, mainly based on flood marks and calculations for restricted areas (Santos, Tavares, & Andrade, 2011), because detailed altimetry data is not available.…”
Section: Introductionmentioning
confidence: 99%